Anxiety, Depression, and Satisfaction With Life Among College Students in China: Nine Months After Initiation of the Outbreak of COVID-19 - Xiao, Pei; Chen, Liang; Dong, Xiaoqin; Zhao, Zhiya; Yu, Jincong; Wang, Dongming; Li, Wenzhen (Frontiers in Psychiatry, 2022)
Background/objective: Mental health problems are common among college students. This study sought to assess the prevalence and risk factors of depressive and anxiety symptoms and well-being among Chinese college students 9 months after initiation of the outbreak of COVID-19. Method: A cross-sectional study (N = 3951, mean age = 19.58) was conducted from September to October 2020. An online survey was used to collect socio-demographic data, and the symptoms of depression and anxiety and satisfaction with life using Disorder 7-Item Scale (GAD-7), the Patient Health Questionnaire 9-Item Scale (PHQ-9) and the 5-items Satisfaction with Life Scale (SWLS). Results: The prevalence of depressive and anxiety symptoms was 59.35% and 54.34%, respectively, and the score of satisfaction with life was 20.51±6.42 among Chinese college students during the pandemic. After controlling for covariates, students in urban (AOR=0.73, 95%CI=0.61-0.87), with good family economic level (AOR=0.77, 95%CI=0.66-0.91), and having psychological counseling (AOR=0.55, 95%CI=0.42-0.73) were positively associated with depression symptoms; meanwhile, higher anxiety symptoms were observed among medical students (AOR=0.81, 95%CI=0.69-0.95). Besides, healthy lifestyle such as regular physical activity and diet was associated with depression and anxiety symptoms. Multiple linear models revealed that medical students (β=0.479, P=0.031), those with good family economic level by self-evaluation (β=1.283, P<0.001 for good; β=3.013, P<0.001 for general), good academic performance by self-evaluation (β=1.786, P<0.001 for good; β=3.386, P<0.001 for general), learning burden (β=1.607, P<0.001 for general; β=2.117, P<0.001 for light), regular physical activity (β=0.859, P<0.001), daily routine (β=1.289, P<0.001), diet (β=1.714, P<0.001) and sufficient sleep (β=1.408, P<0.001) had more score of SWLS (all β>0, P<0.05), while senior students (β=-1.053, P=0.009), students having psychological counseling (β=-1.753, P<0.001) and drinking (β=-0.743, P=0.012) had lower satisfaction with life. Conclusions: These findings suggest that more attention should be paid to psychological health among college students, especially during and after COVID-19 outbreak. Policy makers and educators should help college student develop a healthy lifestyle with regular diet and exercise to promote the psychological health of college students.